?ANTIBACTERIAL ACTIVITY OF EUPHOR- BIA HETEROPHYLLA LINN (FAMILY - EUPHORBIACEAE) (Biological Sciences - PJSIR, 2003)
Dried leaves of Euphorbia heterophylla were used for extraction with three different solvents namely petroleum ether (60-80°C), butanol and ethanol. An in vitro antibacte- rial activity of the plant extracts were evaluated using the agar-diffusion method. The butanolic extract exhibited marked inhibitory action on the growth of Escherichia coli, NCTC 10418, Staphylococcus aureus NCTC 6571, Pseudomo- nas aeruginosa, Klebsiella pneumoniae and Bacillus subtilis at 100 mg/ml.